Macroeconomic Policy Responses to COVID-19: A Case of Indonesia - Acwin Hendra Saputra; I Gede Agus Ariutama (SENTRALISASI, 2021)
The health crisis triggered by the COVID-19 virus has spread to a multidimensional crisis and has a domino effect on the socio-economic and financial sectors. The economic crisis as the impact of the COVID-19 pandemic has become increasingly severe because it was accompanied by lockdown and physical distancing policies which resulted in decreasing productivity in the economy. The purpose of this research is to describe the structured efforts taken by the Government of Indonesia in dealing with the impact of the COVID-19 pandemic. The policy combination adopted by the Government of Indonesia is in the form of policies to issue a series of regulations providing legal certainty and flexibility while still highlighting the accountability. Refocusing and budget reallocation are also taken by the government to provide more flexible space for Ministries/Institutions to contribute to managing the impact of COVID-19. Another policy is the issuance of three stimulus packages and the launch of the National Economic Recovery Program (PEN).